Effects of dietary Mannan oligosaccharide (MOS) on grown, survival rate, intestinal morphology and blood cell count of the golden trevally fish (Gnathanodon specious) - Tram, Dang Tran Tu; Hue, Nguyen Thi Nguyet; Lam, Ho Son; Tai, Nguyen Truong Tan; Ngoc, Dao Thi Hong (Vietnam Journal of Marine Science and Technology, 2019)
The golden trevally fishes (Gnathanodon specious) (2.19 ± 0.23 g) were cultured in glass tanks with density of 20 fishes/tank and they were fed supplemental diets of different MOS concentrations (0; 0.2; 0.4 and 0.6%) for 90 days. Collected data included growth rate, survival rate and some hematological characteristics of this fish. The results demonstrated that MOS supplementation did not affect growth performance, erythrocyte density and blood cell size, however the survival rate was significantly increased. On the other hand, the total number of white blood cells (BC) on the 60th day in the fish fed with MOS supplements (5.78–6.96 × 104TB/mm3) was higher than that in the control group (only 5.43 × 104TB/mm3) with the largest total leukocytes (6.96 ± 0.50 × 104TB /mm3) at 0.2% MOS (p < 0.05)